The Influence of Leadership Style and Organizational Culture on Employee Turnover - Nurasyhari, Miftah; Sapruwan, Muhammad (Talent: Journal of Economics and Business, 2025)
This study aims to investigate the influence of leadership style and organizational culture on employee turnover rates. An effective leadership style and supportive organizational culture can play a crucial role in improving employee job satisfaction, engagement, and loyalty, which in turn can reduce the tendency to leave the company. This study uses a quantitative approach with a survey method to employees in several companies, to measure their perception of the leadership style applied and the organizational culture that exists in their workplace. Data analysis on this study used Smart-PLS. The results of the analysis show that transformational leadership style is negatively related to employee turnover, while an inclusive and supportive organizational culture also plays a significant role in reducing the turnover rate. This research contributes to human resource managers in designing better policies related to leadership management and organizational culture that can reduce employee turnover and improve overall organizational performance.